Advances in Lipoprotein Research 2017
DOI: 10.5772/67141
|View full text |Cite
|
Sign up to set email alerts
|

Role of HDL-Associated Proteins and Lipids in the Regulation of Inflammation

Abstract: Lipoproteins are complexes of lipids and proteins that carry water-insoluble cholesterol in the bloodstream. While cholesterol is required for normal cell function, hypercholesterolemia contributes to the development of cardiovascular disease (CVD). Increased low-density lipoprotein (LDL) is a major risk factor for CVD. Reduced high-density lipoprotein (HDL) levels are inversely related to CVD risk, suggesting a protective role for HDL. Several diseases, including atherosclerosis, diabetes, chronic kidney dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 121 publications
(143 reference statements)
0
17
0
Order By: Relevance
“…One of the most compelling finding of this study is the association of lower baseline HDL levels with SARS-CoV-2 positivity, which corroborates an earlier study, which found association of declining HDL levels with Covid-19 disease severity (10). While causal inferences are beyond the scope of this study, given HDL’s established antioxidant, antithrombotic and anti-inflammatory characteristics, it seems plausible that HDL may play a protective role in preventing the establishment of SARS-CoV-2 infection (19). Alternatively, HDL is now known to transport a wide range of cargo other than cholesterol, such as microRNAs (miRNAs) (20).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most compelling finding of this study is the association of lower baseline HDL levels with SARS-CoV-2 positivity, which corroborates an earlier study, which found association of declining HDL levels with Covid-19 disease severity (10). While causal inferences are beyond the scope of this study, given HDL’s established antioxidant, antithrombotic and anti-inflammatory characteristics, it seems plausible that HDL may play a protective role in preventing the establishment of SARS-CoV-2 infection (19). Alternatively, HDL is now known to transport a wide range of cargo other than cholesterol, such as microRNAs (miRNAs) (20).…”
Section: Discussionmentioning
confidence: 99%
“…Apolipoprotein A1 Major component of the High-Density Lipoprotein (HDL) complex, which is a modulator of innate immune response and inflammation (Fotakis et al, 2019;Gordon et al, 2011;Macpherson et al, 2019;White et al, 2017) . Although it might be that APOA1 levels drop upon the infection, we can also speculate that low APOA1 levels are a risk factor for COVID-19.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…It has been demonstrated that HDL-associated platelet-activating factor acetylhydrolase (PAF-AH) hampers the production and limits the activity of mildly oxidized low-density lipoprotein since it facilitates the hydrolysis of active oxidized phospholipids to lysolipids, which in consequence results in the removal of biologically active lipids in these lipoproteins [37]. ApoA-I has been shown to be the main protein constituent of HDL which binds to and removes lipid hydroperoxides of LDL both in vitro and in vivo and reduces the amount of cholesteryl ester hydroperoxides and phosphatidylcholine hydroperoxides [31,38]. The resulting oxidized HDL was demonstrated to be removed by hepatocytes more rapidly and selectively than native HDL [31].…”
Section: Hdl Role and Functionsmentioning
confidence: 99%